Analisis Hubungan Kecemasan Terhadap Produksi Asi Pada Ibu Postpartum: Literature Review - Wafa Wafiah Purnamawati; Ariani Fatmawati; Bhekti Imansari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: Anxiety is a psychological disorder that often occurs in postpartum. Anxiety experienced by postpartum mothers will have an impact on milk production. The purpose of this study was to analyze the relationship between anxiety and milk production in postpartum. Method: This study used scientific articles with literature review methods and designs with database searches carried out from March to April 2021 through Pubmed, Science Direct, Sage, Google Scholar and ProQuest with the keyword of “Anxiety” OR “Anxiety disorder” OR “Stress” AND ”Breast Milk” OR “Breast output” OR “Breast feeding” OR “Milk Production” AND ”Postpartum” OR “Postnatal” and